UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL ROLE PLAYING PADA TEMA MENYAYANGI TUMBUHAN DAN HEWAN DI KELAS III AN-NAJWA - Rukayah, Rukayah; Nila Lestari, (Jurnal Cakrawala Ilmiah, 2025)
This study aims to improve the learning outcomes of class III elementary school students in An-Najwa, Medan Marelan District, Medan City. This research is a Class Action Research (Clasroom Research). The subjects in this study were 17 students of class III SD. Instruments and data collection techniques used in the research cycle 1 and cycle 2 are observation of student learning activities, teacher teaching observations, test questions and documentation. In Cycle I, the results of observing student learning activities obtained 75% in the good category, the results of observing teacher teaching obtained 77.7% in the good category and the results of observing student learning using the role playing model in cycle 1 obtained an average of 76.64% in the category good. In cycle II the results of observing student learning activities obtained 90% in the very good category, the results of observing teacher teaching obtained 88.8% in the very good category and the results of observing student learning using the role playing model in cycle 2 obtained an average of 94.12% in the very good category . There was an increase in student learning outcomes of 17.65% in cycle II, from 76.64% in cycle 1 to 94.12% in cycle II. Thus it can be concluded that the use of role playing models can improve student learning outcomes on the theme of loving plants and animals in class III of SD An-Najwa